2022
DOI: 10.2147/idr.s390681
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Fungal Superinfections in COVID-19 Patients Hospitalized in an Intensive Care Unit from Timișoara, Romania

Abstract: Purpose Critically ill patients hospitalized in the intensive care unit (ICU) have an increased infection risk. The aim of this study was to determine the bacterial and fungal superinfections rate in Coronavirus disease 2019 (COVID-19) patients stationed in the ICU, identify risk factors associated with their development and to determine whether superinfection plays a role in patients’ outcome in this population. Patients and Methods In this retrospective, non-intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Nonetheless, PCT could be used as a helpful tool to guide antibiotic therapy for COVID-19 (32). In line with the ndings of previous studies (2,12), multivariate logistic analysis indicated that central venous and urinary catheters are associated with increased infection risk. The most common infection source of catheters is intradermal and catheter interface contamination by organisms, which may come from the patient's skin or from healthcare workers' hands.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Nonetheless, PCT could be used as a helpful tool to guide antibiotic therapy for COVID-19 (32). In line with the ndings of previous studies (2,12), multivariate logistic analysis indicated that central venous and urinary catheters are associated with increased infection risk. The most common infection source of catheters is intradermal and catheter interface contamination by organisms, which may come from the patient's skin or from healthcare workers' hands.…”
Section: Discussionsupporting
confidence: 75%
“…The long-term impacts of viral and bacterial/fungal coinfections on antimicrobial resistance are severe public problems (9). It is di cult for clinicians to identify coinfections early because of similar symptoms and signs, thus leading to a high rate of inappropriate prescription (10)(11)(12). Early empiric antibiotic use varied from 27-84% across different hospitals (10).…”
mentioning
confidence: 99%
“…In Romania, one of the first authors to observe that the differences between patients with severe and non-severe cases were not statistically significant was Totan et al [56]. Other studies had similar findings [28,32,60].…”
Section: Transaminase Levels and Other Hepatic Markersmentioning
confidence: 93%
“…Elevated BUN levels may indicate impaired kidney function, which is a common complication of severe COVID-19 disease. Many authors have reported high levels in data from Romania and suggested a link with the severity of the infection, as well as a possible marker for severity [26,[32][33][34]40,62]. Some authors have reported other common renal markers such as creatinine and urea [30,40,59].…”
Section: Blood Urea Nitrogen (Bun) and Other Renal Markersmentioning
confidence: 99%
“…2 Another study found that the presence of a central venous catheter was a significant risk factor for bacterial or fungal superinfections in COVID-19 patients, as was the number of days the patient remained catheterized. 3 Fifth, the authors should have mentioned whether any patient had intestinal colonization of carbapenem-resistant Enterobacterales (CRE), as a prospective study found that it was a predictor of superinfections in COVID-19 patients, resulting in a significantly prolonged length of hospital stay in CRE-colonized versus noncolonized patients (p < 0.001). 2 Furthermore, the authors should have highlighted whether any patient had received corticosteroid treatment or immunomodulatory drugs, such as tocilizumab.…”
mentioning
confidence: 99%